2019
DOI: 10.3390/metabo9080159
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adipocyte Fatty Acid-Binding Protein Level is Negatively Associated with Vascular Reactivity Index Measured by Digital Thermal Monitoring in Kidney Transplant Patients

Abstract: Adipocyte fatty acid-binding protein (A-FABP) is abundantly found in mature adipocytes and is involved in cardiovascular disease. Our aim is to investigate the association between serum A-FABP levels and endothelial function among kidney transplant (KT) patients. Fasting blood samples were obtained from 80 KT patients. Serum A-FABP levels were measured using a commercially available enzyme immunoassay kit. Endothelial function and vascular reactivity index (VRI) were measured using digital thermal monitoring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The endothelium is a target of injury even in renal transplantation patients. We recently found that endothelial dysfunction measured by VRI, was correlated with serum adipocyte fatty acid binding protein, which is a potential biomarker of CVD [19]. Here in our research, we similarly assessed endothelial function by using a non-invasive method, the DTM, and found that as the renal function worsened, the values of VRI decreased.…”
Section: Discussionmentioning
confidence: 59%
“…The endothelium is a target of injury even in renal transplantation patients. We recently found that endothelial dysfunction measured by VRI, was correlated with serum adipocyte fatty acid binding protein, which is a potential biomarker of CVD [19]. Here in our research, we similarly assessed endothelial function by using a non-invasive method, the DTM, and found that as the renal function worsened, the values of VRI decreased.…”
Section: Discussionmentioning
confidence: 59%
“…The endothelial function of all participants was measured using an FDA-approved device (Endothelix Inc., Houston, TX, USA) with DTM method, with BP cuffs and skin temperature sensors placed on both upper arms and index fingers, respectively [ 32 , 33 ]. In performing the DTM method, we first stably positioned both hands for 3 min, inflated the BP cuff to 50 mmHg greater than the systolic BP, and finally, deflated the BP cuff in 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…VRI has been defined as the maximal temperature difference between the rebound curve and the zero reactivity curves during the period of reactive hyperemia period, calculated by the VENDYS software. VRIs were found to range from 0.0 to 3.5; a VRI of less than 1.0 indicated poor vascular reactivity; a VRI ranging from 1.0 to 1.9, intermediate vascular reactivity; and a VRI of 2.0 or greater, good vascular reactivity [7,11].…”
Section: Endothelial Function Measurementsmentioning
confidence: 98%
“…Participants were weighed, wearing lightweight clothing without shoes, to the nearest 0.5 kg, and body height was measured to the nearest 0.5 cm. Body mass index was calculated as the weight in kilograms divided by the height in meters squared [11].…”
Section: Anthropometric Analysismentioning
confidence: 99%
See 1 more Smart Citation